Barriers to Parents in Handling Children with Down Syndrome in Border Areas - Jiu, Cau Kim; Nur Jannah (Indonesian Journal of Disability Studies, 2024)
Access and facilities for children with Down syndrome are still very limited, especially in border areas far from urban areas. The remote geographical location becomes an obstacle for parents in utilizing health and educational facilities for children with Down syndrome. This qualitative descriptive research aims to determine the obstacles faced by families in dealing with children with Down syndrome in border areas. Participants in this study were 6 parents of children with Down syndrome who were selected using the purposive sampling method. This research was conducted in one of the Indonesia-Malaysia border areas in West Kalimantan. The research results revealed three (3) themes of parental barriers in dealing with Down syndrome children, such as 1) Family barriers in getting special education for children, 2) Barriers in handling children, and 3) Limited information. Therefore, regional and central government support is very necessary in providing adequate education and health facilities for people with disabilities at the border